The Post-Keynesian Economics Study Group - After 20 Years - Mark (M.G.) Hayes (Intervention. European Journal of Economics and Economic Policies, 2008)
First paragraph: The Post-Keynesian Economics Study Group (or PKSG, as it is usually abbreviated) was founded in 1988 by Philip Arestis and Victoria Chick with financial support from the UK Economic and Social Research Council (ESRC). The purpose of the Study Group is to encourage collaboration among scholars and students of Post-Keynesian economics, defined by the founders broadly »as a theoretical approach that drew upon the work of Keynes, Kalecki, Joan Robinson, Kaldor and Sraffa, and distinguished itself by its insistence that history, social structure and institutional practice be embodied in its theory and reflected in its policy recommendations« (Lee 2007a). The central feature of this approach has been further articulated by Arestis (1996) as the principle of effective demand, which can be approached from the perspectives of various intellectual traditions, including those of Keynes himself (closest to Marshall and the modern Neo-Classicals) and of Kalecki (drawing on Marx), informed by an emphasis on institutions deriving ultimately from Veblen. These traditions cover the contributions of Robinson and Kaldor, and Sraffa's critique of Neo-Classical economics, although the positive Neo-Ricardian programme is best regarded as a separate school of thought (Arestis et al. 1999).
Keywords: 330